My last duchess ebook - James, Eloisa (Wildes of Lindow Castle, 2020)
New York Times bestselling author Eloisa James returns to the Wildes series with a prequel about the Wilde children's parents, Hugo, Duke of Lindow, and Ophelia, Lady Astley. Every Duke needs a Duchess... Hugo Wilde, the Duke of Lindow, has a drafty castle, eight naughty children—and no wife. Ophelia, Lady Astley, has a fine house, one well-behaved daughter—and no husband. Hugo takes one look at Ophelia and loses his heart, but she doesn't want more children or a castle. She takes one look at him and heads for her carriage. Desperate to find a duchess, Hugo identifies an appropriate lady to woo. Yet when he meets Ophelia again, the duke realizes that he will marry her, or no one. Now he faces the greatest challenge of his life. He must convince Ophelia that their blazing sensuality, his exquisite castle, and his eight charming children add up to a match made in heaven. When a duke finds his duchess, can he win her heart?